AB0268 MORTALITY RATE OF RHEUMATOID ARTHRITIS PATIENTS EVEN IN THE NEW ERA OF BIOLOGICS IS HIGHER THAN THE CONTROL GROUP: EIGHT YEARS OF THE TOMORROW STUDY. (June 2019) - Mandai, Koji; Koike, Tatsuya; Sugioka, Yuko; Inui, Kentaro; Okano, Tadashi; Yamada, Yutaro; Tada, Masahiro; Mamoto, Kenji; Anno, Shohei; Nakamura, Hiroaki
Abstract : Background: Patients with rheumatoid arthritis (RA) have a high mortality rate compared to the general population 1 . However, the mortality rate of patients with RA might be improved by advances in therapy 2 . Objectives: We investigated the risk factors for mortality in patients with RA from TOMORROW study. Methods: This study included 413 participants, comprising 208 patients with RA and 205 age- and sex- matched healthy volunteers (Vo) from the prospective "TOMORROW" cohort study that has been ongoing since 2010 were included in this study (women, 84%; mean age, 58 years old). Median disease duration was 10.3 years. Results: The rate of accomplishment for 8 years was 83.2% in the RA group and 92.7% in the Vo group. There were 14 deaths in the RA group (8.7/1000 person-years) and two in the Vo group (1.2/1000 person-years) (p=0.0025) for 8 years. Infection was the most common cause of death in the RA group (43%). Cox proportional hazard analysis showed that having RA was significant risk factor for death (hazard ratio [HR]: 6.9, 95%CI: 1.6 - 30.4, p=0.01) adjusting by age (Figure). In the RA group, glucocorticoid (GC) use (HR: 3.6, 95%CI: 1.1 -10.4, p=0.032) was significant risk factor for death. Disease activity, duration of disease, use of biological products, use of methotrexate, presence of cardiovascular disease, and smoking were not significant factor. Conclusion: RA was still significant risk factor of death. GC use was independent factors of death in RA patients. References: [1] van den Hoek J, Boshuizen HC, Roorda LD, et al. Mortality in patients with rheumatoid arthritis: a 15–year prospective cohort study. Rheumatol Int (2017) 37:487–493 [2] Lacaille D, Avina-Zubieta JA, Sayre EC, et al. Improvement in five-year mortality in rheumatoid arthritis compared to the general population – closing the mortality gap. Ann Rheum Dis. 2017June; 76(6): 1057–1063. Disclosure of Interests: Koji Mandai: None declared, Tatsuya Koike Speakers bureau: AbbVie, Astellas Pharma Inc., Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Yuko Sugioka: None declared, Kentaro Inui Speakers bureau: Takeda Pharmaceutical, Pfizer Japan, Daiichi-Sankyo Co.Ltd., Abbvie, Mitsubishi Tanabe Pharma Corporation, Janssen Pharmaceutical, Chugai Pharmaceutical, Ono Pharmaceutical, Eisai Co.Ltd., Eli-Lilly, Nippon Kayaku Co., Ltd., Maruho Co., Ltd, Kaken Pharmaceutical Co., Ltd., Tadashi Okano Speakers bureau: AbbVie, Yutaro Yamada Speakers bureau: Abbvie, Chugai, Mitsubishi Tanabe, Masahiro Tada Speakers bureau: Abbvie, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Ono Pharmaceutical, Pfizer Japan, Takeda Pharmaceutical, Kenji Mamoto: None declared, Shohei Anno: None declared, Hiroaki Nakamura: None declared